NK Cell Isolation from Liver Biopsies: Phenotypic and Functional Analysis of Low Cell Numbers by Flow Cytometry - Li, Ning; Puga Yung, Gisella L.; Pradier, Amandine; Toso, Christian; Giostra, Emiliano; Morard, Isabelle; Spahr, Laurent; Seebach, Jörg D. (Frontiers in Immunology, 2013)
Natural killer (NK) cells are considered to play a critical role in liver disease. However, the available numbers of intrahepatic lymphocytes (IHL) derived from liver biopsies (LB) for ex vivo analysis of intrahepatic NK cells is very limited; and the isolation method may hamper not only yields and viability, but also phenotype and function of IHL. The aim of the present study was therefore to (1) refine and evaluate the cell yields and viability of a modified isolation protocol from standard size needle LB; and (2) to test the effects of mechanical dissociation and enzymatic tissue digestion, as well as the analysis of very low cell numbers, on the phenotype and function of intrahepatic NK cells. Peripheral blood mononuclear cells (PBMC) and IHL, freshly isolated from the peripheral blood, LB (n = 11) or partial liver resections (n = 5), were used for phenotypic analysis by flow cytometry. NK cell function, i.e., degranulation and cytokine production, was determined by staining of CD107a and intracellular IFN-γ following in vitro stimulation. The mean weight of the LB specimens was 9.1 mg, and a mean number of 7,364 IHL/mg were obtained with a viability of >90%. Exposure of IHL and PBMC to 0.5 mg/ml collagenase IV and 0.02 mg/ml DNase I for 30 min did affect neither the viability, NK cell function, nor the percentages of CD56+, NKp46+, and CD16+ NK cells, whereas the level of CD56 surface expression was reduced. The phenotype of LB-derived NK cells was reliably characterized by acquiring as few as 2,500 IHL per tube for flow cytometry. The functional assay of intrahepatic NK cells was miniaturized by culturing as few as 25,000 IHL in 25 μl (106/ml) using 96-well V-bottom plates with IL-2 and IL-12 overnight, followed by a 4 h stimulation with K562 cells at a NK:K562 ratio of 1:1. In summary, we report reliable phenotypic and functional analyses of small numbers of intrahepatic NK cells isolated from LB specimens providing us with a tool to better address the emerging role of human NK cell immunobiology in liver diseases.